Marketing of Kabuli and Desi chickpeas by smallholder farmers in Eastern Shewa Zone - Demissie, M. (Haramaya University, 2011)
An understanding of the market for smallholder farmers’ crops can provide clues to the potential market for their crops. The main objective of this study was thus to analyze the marketing performance of Kabuli and Desi chickpeas in three districts of east Shewa zone. It investigated the socio-economic, demographic, and institutional factors and other marketing attributes that affect farm gate-prices, season price fluctuations and marketable surplus of chickpeas in the study areas. A sample of 700 randomly selected households was interviewed using a structured questionnaire. Secondary data from different sources were also used. Both descriptive and econometric methods were used to analyze the data. The conceptual and empirical evidence suggests that improving smallholder farmers’ awareness for the uptake of improved Kabuli varieties for which the marginal values of varieties are considerably high relative to the price of the inputs would improve farm-gate net returns and prices received by small producers. The marketable surplus will also be improved if farmers switch to production of improved varieties of Kabuli chickpeas. Supplementary production relation ship between crop and livestock enterprises was found to be one of the important solutions to alleviation of high price variability that reduces competitiveness of chickpea marketing. In addition to the crop and livestock supplementary enterprise relation ship, moving for off-farm income activities with out affecting negatively the crop and livestock farming was found another alternative to alleviation of the high price variability problems. The study, however, ascertains that smallholder farmers need to know not only how to produce but first need to know and learn how to identify preferable potential buyers that will enhance competitiveness of chickpea market.